Diffusion-weighted imaging of the abdomen at 3.0 Tesla: Image quality and apparent diffusion coefficient reproducibility compared with 1.5 Tesla - Rosenkrantz, Andrew B.; Oei, Marcel; Babb, James S.; Niver, Benjamin E.; Taouli, Bachir (Journal of magnetic resonance imaging, 2011)
Purpose To compare single‐shot echo‐planar imaging (SS EPI) diffusion‐weighted MRI (DWI) of abdominal organs between 1.5 Tesla (T) and 3.0T in healthy volunteers in terms of image quality, apparent diffusion coefficient (ADC) values, and ADC reproducibility. Materials and Methods Eight healthy volunteers were prospectively imaged in this HIPAA‐compliant IRB‐approved study. Each subject underwent two consecutive scans at both 1.5 and 3.0T, which included breathhold and free‐breathing DWI using a wide range of b‐values (0 to 800 s/mm2). A blinded observer rated subjective image quality (maximum score= 8), and a separate observer placed regions of interest within the liver, renal cortices, pancreas, and spleen to measure ADC at each field strength. Paired Wilcoxon tests were used to compare abdominal DWI between 1.5T and 3.0T for specific combinations of organs, b‐values, and acquisition techniques. Results Subjective image quality was significantly lower at 3.0T for all comparisons (P = 0.0078– 0.0156). ADC values were similar at 1.5T and 3.0T for all assessed organs, except for lower liver ADC at 3.0T using b0‐500‐600 and breathhold technique. ADC reproducibility was moderate at both 1.5T and 3.0T, with no significant difference in coefficient of variation of ADC between field strengths. Conclusion Compared with 1.5T, SS EPI at 3.0T provided generally similar ADC values, however, with worse image quality. Further optimization of abdominal DWI at 3.0T is needed. J. Magn. Reson. Imaging 2011;33:128–135. © 2010 Wiley‐Liss, Inc.